STUDYING FANDOM ONLINE: A CASE STUDY OF TWICE AND STRAY KIDS FANDOM ON FAN FICTION PRACTICES OF @ESKALOKAL AND @GABENERTWICE ON TWITTER - Cendera Rizky Bangun; Nareswari Kumaralalita; Gabriela Frederika Febe Sukur (ASPIRATION Journal, 2020)
Popular culture is developing over time and fanfiction is product of popular culture. Fanfiction is a work of fiction created by fans as a sense of involvement (a culture of participation) between them and their idols. In addition to creating a sense of "closeness" with his idol, fan fiction can also provide a feeling of satisfaction for fans who want an ending or even a whole new world for their idols. Which later became one of the genres in Fan Fiction and was called the Alternative Universe. Fan fiction usually has a fairly long format, with platforms like Wattpad or Asian FanFic on the site, now the trend is changing to social media platforms, especially Twitter. Using @eskalokal and @gabenertwice as research objects, the method in this research is a qualitative method. Informants for this research are writers and readers of @eskalokal and @gabenertwice. After data collected, the next step is categorizing the interview transcript based on the informant's own words or in vivo coding. The result of this research is that the changing platform of fan fiction is more suitable for the informants. It turns out that many fans who initially liked fan fiction using Wattpad or website switch to the social media alternative universe because their attention span has decreased.